2017
DOI: 10.1111/bcpt.12697
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides, but not Angiotensin ll, lnduces Direct Pro‐lnflammatory Effects in Cultured Mouse Arteries and Human Endothelial and Vascular Smooth Muscle Cells

Abstract: Angiotensin II (Ang II) might induce pro-inflammatory effects directly in the vascular wall independently of its haemodynamic effects. The aim of our study was to investigate the putative direct pro-inflammatory and vasomotor effects of Ang II and compare to those of lipopolysaccharides (LPS) in mouse isolated mesenteric resistance-sized arteries (MRA) supported by experiments in cultured human primary endothelial and vascular smooth muscle cells. Results showed that 24-hr organ culture of mouse MRA with 10 nM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…In contrast to the high concentration of Ang II at repeated dose of live bacteria, we found a down regulation of AGTR1 and AGTR2 at the mRNA level. Similar results with human saphenous vein cells (VSMC) and rat aortic smooth muscle (HASMC) suggest that high concentrations of Ang II can induce in vitro gen downregulation or desensitization/internationalization of AGTR1 48,58,59 or AGTR2 57 . However, additional studies are required to identify the role of these receptors in endothelial dysfunction at repeated dose of periodontopathogens.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…In contrast to the high concentration of Ang II at repeated dose of live bacteria, we found a down regulation of AGTR1 and AGTR2 at the mRNA level. Similar results with human saphenous vein cells (VSMC) and rat aortic smooth muscle (HASMC) suggest that high concentrations of Ang II can induce in vitro gen downregulation or desensitization/internationalization of AGTR1 48,58,59 or AGTR2 57 . However, additional studies are required to identify the role of these receptors in endothelial dysfunction at repeated dose of periodontopathogens.…”
Section: Discussionsupporting
confidence: 54%
“…Regarding the association between Ang II and the release of proinflammatory molecules such as IL8, IL6 and MCP1, there is no evidence with periodontopathogens, while some evidence have been reported Escheriria coli- LPS ( E. coli-LPS ) 48,58,59 , suggesting a synergistic effect between live- P. gingivalis stimulus and Ang II.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of evidence suggests that TLR4 modulates endothelial inflammation and atherosclerotic disease [32]. LPS stimulates IL-6, MCP-1 and VCAM-1 mRNA expression in endothelial cells [33]. Isobavachalcone significantly retards leukocyte adhesion to brain endothelial cell via the inhibition of TLR4 signaling [34].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Bacchiega et al found that the IL-6-blocking agent tocilizumab significantly reduced CRP concentrations, together with parameters of systemic inflammation [26]. IL-6 has many other functions, including activation of macrophages [27, 28] and stimulation of endothelial [29, 30] and vascular smooth muscle cells [31, 32]. Although IL-6 and miR-29b both have a number of clear effects on different stages in the formation of atherosclerosis and are, individually, important markers for CVD, we have shown that that the combination of miR-29b and IL-6 offers a better predictive marker for atherosclerosis than either miR-29b or IL-6 alone.…”
Section: Discussionmentioning
confidence: 99%